PENERAPAN KRITERIA SINDROM KERENTAAN PADA LANSIA DI SENTRA VAKSINASI COVID-19 DOSIS LANJUTAN UNIVERSITAS TARUMANAGARA - Marcella Erwina Rumawas; Noer Saelan Tadjuddin; Shirly Gunawan; Zita Atzmardina (Jurnal Bakti Masyarakat Indonesia, 2022)
The advanced dose of COVID-19 vaccination aims to maintain the level of immunity and extend the period of protection against SARS-CoV-2 virus infection, given especially to vulnerable groups of people, one of which is the elderly. Currently, the number of elderly people receiving COVID-19 vaccination is still inadequate, partly due to public misinformation regarding the side effects of post-vaccination in the elderly. It has been known that vaccination in the elderly must be carried out with extra care because of the frailty of the elderly.  Therefore, to ensure that vaccination for the elderly is effective and optimal, the feasibility of receiving a COVID-19 vaccination needs to be determined through screening for frailty syndromes. The advanced-dose COVID-19 Vaccination Center at Tarumanagara University, in partnership with the Grogol Petamburan District Health Center, West Jakarta, was held on February 2-4, 2022. Besides the general criteria for vaccination, which included history of diseases and the results of measuring body temperature and blood pressure, the medical team from the Faculty of Medicine Tarumanagara University applied the criteria for frailty syndrome to the elderly, namely difficulty climbing 10 stairs or walking 100-200 meters, often feeling tired, have at least 5 of 11 chronic diseases and experienced significant weight loss in the past year. Elderly was not eligible to receive COVID-19 vaccine if there were >2 conditions of vulnerability were found.  Of the 45 elderly who took part in the activity, none had a frailty condition >2, so a further dose of COVID-19 vaccination could be given. ABSTRAK: Vaksinasi COVID-19 dosis lanjutan bertujuan untuk mempertahankan tingkat kekebalan serta memperpanjang masa perlindungan terhadap infeksi virus SARS-CoV-2, diberikan terutama pada kelompok masyarakat rentan, salah satunya adalah lansia. Saat ini jumlah lansia yang menerima vaksinasi COVID-19 belum memadai, diantaranya disebabkan media informasi publik mengenai efek samping pasca vaksinasi pada lansia.  Telah diketahui bahwa vaksinasi pada lansia harus dilakukan dengan ekstra hati-hati karena adanya kondisi kerentaan (frailty) pada lansia.  Sebab itu, untuk memastikan pemberian vaksinasi pada lansia efektif dan optimal, kelayakan menerima vaksinasi COVID-19 perlu ditentukan melalui penapisan sindrom kerentaan.  Sentra Vaksinasi   COVID-19 dosis lanjutan di Universitas Tarumanagara, bermitra dengan Puskesmas Kecamatan Grogol Petamburan Jakarta Barat, diselenggarakan pada tanggal 2-4 Februari 2022. Selain kriteria umum layak vaksinasi yang mencakup hasil pengukuran suhu tubuh dan tekanan darah serta riwayat penyakit, tim medis dari Fakultas Kedokteran Universitas Tarumanagara menerapkan kriteria sindrom kerentaan pada sasaran lansia, yaitu kesulitan naik 10 anak tangga, kesulitan berjalan 100-200 meter, sering merasa kelelahan, memiliki minimal 5 dari 11 penyakit kronik dan mengalami penurunan berat badan yang bermakna dalam setahun terakhir.  Jika didapatkan >2 kondisi kerentaan, maka lansia belum layak divaksinasi COVID-19. Dari 45 lansia yang menghadiri kegiatan tersebut, tidak didapatkan lansia dengan kondisi renta >2 sehingga dinyatakan layak diberikan vaksinasi COVID-19 dosis lanjutan.